AN MANAGEMENT ORGANIC FERTILIZER COCONUT COIL LIQUID AND CHICKEN CAGE INCREASE THE GROWTH AND PRODUCTION OF ALLIUM ASCALONICUM L - Erlita Chaniago; Farida Hariani; Purwanto Purwanto (Jurnal Ekonomi, 2023)
This research was conducted at Jalan Pintu IV, Alley Pond Jaka, Padang Bulan, Medan, Medan Johor District, North Sumatra Province. This study used a factorial randomized block design with 2 factors studied and 3 repetitions where the first factor was liquid organic coconut fiber fertilizer (B), which consisted of 3 levels, namely B0 = without coconut coir liquid organic fertilizer B1 = 1.5 L/Plot, B2 = 3L/Plot. The second factor was chicken manure consisting of 4 levels, namely A0 = without chicken manure, A1 = 2 Kg/Plot, A2 = 4 Kg/Plot, A3 = 6 Kg/Plot. Chicken manure has a significant effect on all observed parameters while for its interaction it has a significant effect on the number of tillers parameter.